2014
DOI: 10.4103/2277-9175.129375
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effects of tensile and compressive loadings on human femur bone

Abstract: Background:Fragile fractures are most likely manifestations of fatigue damage that develop under repetitive loading conditions. Numerous microcracks disperse throughout the bone with the tensile and compressive loads. In this study, tensile and compressive load tests are performed on specimens of both the genders within 19 to 83 years of age and the failure strength is estimated.Materials and Methods:Fifty five human femur cortical samples are tested. They are divided into various age groups ranging from 19-83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 19 publications
4
65
0
1
Order By: Relevance
“…Scaffold (c) had the lowest dry and wet compressive moduli of 0.40 ± 0.005 and 0.34 ± 0.1 GPa, respectively. The compressive moduli of human cortical femur bone ranges from 0.338 ± 0.179 to 0.404 ± 0.314 GPa and are similar to those recorded in this study. Statistically significant differences were found for each design and for the dry/wet conditions.…”
Section: Resultssupporting
confidence: 85%
“…Scaffold (c) had the lowest dry and wet compressive moduli of 0.40 ± 0.005 and 0.34 ± 0.1 GPa, respectively. The compressive moduli of human cortical femur bone ranges from 0.338 ± 0.179 to 0.404 ± 0.314 GPa and are similar to those recorded in this study. Statistically significant differences were found for each design and for the dry/wet conditions.…”
Section: Resultssupporting
confidence: 85%
“…In fact, the compressive strength of the HA dry -derived samples was around 60 MPa, while HA wet -derived materials achieved significantly higher values (around 300 MPa), comparable or even higher than those of human cortical bones 46,47 and suggesting a possible mechanical role in orthopedic applications. In fact, the compressive strength of the HA dry -derived samples was around 60 MPa, while HA wet -derived materials achieved significantly higher values (around 300 MPa), comparable or even higher than those of human cortical bones 46,47 and suggesting a possible mechanical role in orthopedic applications.…”
Section: Resultsmentioning
confidence: 89%
“…Niu et al [13] used carbamide particles as space-holders, and the final porosity was 55%-75%. The samples were produced by loose sintering, the Young's modulus of these samples was 3-6.4 GPa, and the plateau stress varied between 10 and 35 MPa [13], which is too low for load-bearing applications, since a typical human bone exhibits a compressive strength ranging between 150 and 300 MPa [14]. In the present work, it will be demonstrated that even samples with high porosity have a high strength when they are produced by hot-pressing instead of sintering.…”
Section: Introductionmentioning
confidence: 99%